VD_FINDINFO Jug / 2015 / 481 vom 25. Februar 2014 - VD Tribunal cantonal (2014)
TRIBUNAL FÉDÉRAL, ESCROQUERIE, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, RETOUR | 146 al. 1 CP, 42 CP, 43 al. 1 CP, 44 al. 1 CP, 47 CP, 107 al. 2 LTF